3(4K-1/3)

Simple and best practice solution for 3(4K-1/3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4K-1/3) equation:


K in (-oo:+oo)

3*(4*K-(1/3)) = 0

3*(4*K-1/3) = 0

( 3 )

3 = 0

K belongs to the empty set

( 4*K-1/3 )

4*K-1/3 = 0 // + 1/3

4*K = 1/3 // : 4

K = 1/3/4

K = 1/12

K = 1/12

See similar equations:

| -3x+14=-30 | | -7+7(-3x-5)=-175 | | -35+6x=25+x | | R+14=8(x+7) | | 8x+3.90=12x+2.10-3 | | 3(X-5)-5(1-X)+4=0 | | x*x*x=94.72 | | (5x-2)+(3x+4)=90 | | 24=-2x+2 | | 3.4=-t/8.5 | | x+85+92=90 | | 1.5y-4.5x=21 | | 2y+x=3x-y-6 | | 10(7j+10)= | | x*x*x=37*1.6*1.6 | | -5/6m=-60 | | 5x*2=10 | | 2n+5=-21 | | -4x+2(3x-5)=-20 | | x^2-9y=6 | | Y-9.50=9.5(X-1) | | 3x-30=-14 | | 3/4x=2/7 | | 7n=3n-5-3 | | (w+3)(w-3)=0 | | -5(6r-8)=r | | (x+15)+(x-14)= | | 6x-2(x+1)=2(5x+5) | | -16+6X=2X+40 | | 3x-2(6x-17)=-20 | | 8+x(3)=18 | | 3(2x+1)+3=8 |

Equations solver categories